5-Aminoimidazole-4-carboxamide ribonucleoside induces differentiation of acute myeloid leukemia cells. Issue 10 (October 2014) - Lalic, Hrvoje; Dembitz, Vilma; Lukinovic-Skudar, Vesna; Banfic, Hrvoje; Visnjic, Dora
Abstract Adenosine monophosphate (AMP)-activated kinase (AMPK) modulators have been shown to exert cytotoxic activity in hematological malignancies, but their role in the differentiation of acute myeloid leukemia (AML) is less explored. In this study, the effects of AMPK agonists on all-trans retinoic acid (ATRA)-mediated differentiation of acute promyelocytic leukemia (APL) and non-APL AML cell lines were investigated. The results show that AMPK agonists inhibit the growth of myeloblastic HL-60, promyelocytic NB4 and monocytic U937 cells. 5-Aminoimidazole-4-carboxamide ribonucleoside (AICAR), an AMPK activator, enhances ATRA-mediated differentiation of NB4 cells. In U937 cells, AICAR alone induces the expression of cell surface markers associated with mature monocytes and macrophages. In both cell lines, AICAR increases the activity of mitogen-activated protein kinase (MAPK), and the presence of a MAPK inhibitor reduces the expression of differentiation markers. These results reveal beneficial effects of AICAR in AML, including differentiation of non-APL AML cells.